Interpolation of air quality monitoring data in an urban sensitive area: the Oporto/Asprela case - Fontes, Tânia (2012)
At urban level, the representativity of air quality measurements is low which requires a dense measurement network and/or the use of complementary techniques for the air quality evaluation. Based on data from an air quality campaign and from the national air quality network, this article explores two interpolation methods in order to select the best for the air quality concentration field estimation in a sensitive urban area. The preliminary analysis indicates that the IDW is the best air quality interpolation method for the study domain.A nível urbano, a representatividade das medições da qualidade do ar é baixa, exigindo uma densa rede de medição e/ou recurso a técnicas complementares para a avaliação da qualidade do ar. Baseado em dados de uma campanha e da rede nacional de qualidade do ar, este artigo explora dois métodos de interpolação para seleccionar o melhor método de estimativa da qualidade do ar numa área urbana sensível. A análise preliminar indica que o IDW é o melhor método de interpolação para o domínio de estudo.